Attentional load effects on emotional content in face working memory. Issue 7 (July 2023) - Valenti, Livia; Wada Pucci, Isabella; Basso Garcia, Ricardo; Jackson, Margaret C; Galera, Cesar
This study investigated the role of attentional resources in processing emotional faces in working memory (WM). Participants memorised two face arrays with the same emotion but different identities and were required to judge whether the test face had the same identity as one of the previous faces. Concurrently during encoding and maintenance, a sequence of high- or low-pitched tones (high load) or white noise bursts (low load) was presented, and participants were required to count how many low-tones were heard. Experiments 1 and 2 used an emotional and neutral test face, respectively. The results revealed a significant WM impairment for sad and angry faces in the high-load versus low-load condition but not for happy faces. In Experiment 1, participants remembered happy faces better than other emotional faces. In contrast, Experiment 2 showed that performance was poorer for happy than sad faces but not for angry faces. This evidence suggests that depleting attentional resources has less impact on WM for happy faces than other emotional faces, but also that differential effects on WM for emotional faces depend on the presence or absence of emotion in the probe face at retrieval.